Smart home comfort and energy conservation using internet of things - Tobiloba Emmanuel Somefun; Ademola Abdulkareem; Claudius O. Awosope; Oluwatobiloba Akanji (Universitas Ahmad Dahlan, 2022)
This new work presents a home automation system which employs internet of things (IoT) technology. This technology streamlines the design with an accurate home automation system which guides against the issues of energy wastage and excessive expenditure on the present systems of the utility company and the consumers. The system deploys a 32-bit ESP8266 system on chip (SoC) wireless fidelity (Wi-Fi) module which is linked to some sensors through a microcontroller for data communication. User friendly remote access, operation and management of the system are achieved through a mobile/web graphic user interface application. Daniel hall of students' residence at Covenant University is the location chosen for the deployment of prototype designed, the overall system achieved approximately 17% savings in energy consumption which in turn reduces the cost of energy usage for the same comform level.